Green Supply Chain Implementation on Tempeh Industry in North Jakarta - Nasution, Nursery Alfaridi S; Nofrisel, Nofrisel; Andriyan, Andriyan; Sekar Widyastuti Pratiwi; Muhammad Luqmanul Hakim (Dinasti International Journal of Digital Business Management, 2024)
Qualitative research relies on both primary and secondary data. This research aims to elucidate the implementation of green supply chain management in the tempeh industry, as well as to illustrate how green supply chain management can be applied to effectively manage waste generated by the tempeh industry. The ultimate goal is to promote environmental sustainability and mitigate the issue of industrial waste, thereby ensuring a clean and healthy environment. The findings of this study indicate that the integration of green supply chain management in the tempeh industry has been effectively executed. The utilization of raw resources also aligns with the concepts of green supply chain. In addition to that, there is excellent cooperation within the supply chain. Nevertheless, there are still areas for improvement in the supply chain flow of the green supply chain implementation in the tempe business in North Jakarta. Additional empirical study is required to examine the aspects that contribute to the performance of green supply chains.